Impact of lesion length on the outcomes of chronic total occlusion percutaneous coronary intervention: Insights from the PROGRESS‐CTO registry. Issue 4 (5th February 2023) - Rempakos, Athanasios; Simsek, Bahadir; Kostantinis, Spyridon; Karacsonyi, Judit; Choi, James W.; Poommipanit, Paul; Khatri, Jaikirshan J.; Jaber, Wissam; Rinfret, Stephane; Nicholson, William; Gorgulu, Sevket; Jaffer, Farouc A.; et al.
Abstract: Background: The impact of occlusion length on the procedural techniques and outcomes of chronic total occlusion (CTO) percutaneous coronary intervention (PCI) has received limited study. Methods: We examined the clinical and angiographic characteristics and procedural outcomes of 10, 335 CTO PCIs at 42 US and non‐US centers between 2012 and 2022. The cohort was divided into two groups based on lesion length (≥20 mm vs. <20 mm). Results: Long lesions were present in 7208 (70%) patients. Comorbidities were more common in patients with long CTOs. Compared with short lesions, long lesions had higher J‐CTO score (2.8 ± 1.1 vs. 1.3 ± 1; p  < 0.001) and retrograde wiring was more often the initial (15.5% vs. 4.0%; p  < 0.001) and successful (22.8% vs. 8.2%; p  < 0.001) crossing strategy. Long lesions were more likely to require longer procedure (123 vs. 91 min; p  < 0.001) and fluoroscopy (47.1 vs. 32.2 min; p  < 0.001) time, larger contrast volume (218 vs. 200 mL; p  < 0.001) and higher air kerma radiation dose (2.4 vs. 1.7 Gy; p  < 0.001). After adjusting for potential confounders, long lesions were associated with lower technical success (odds ratio [OR]: 0.91 per 10 mm increase; 95% confidence interval [CI]: 0.88, 0.94) and higher major adverse cardiovascular events (MACE) (OR: 1.08 per 10 mm increase; 95% CI: 1.02, 1.15). Conclusions: CTO PCI of long occlusions is independently associated with lower rates of technical success and higher rates of in‐hospital MACE.